Endemic diseases and agricultural productivity: Challenges and policy response - (:unkn) unknown (My University, 2010)
Contrary to Asian countries, the agricultural sector in Africa has not benefited from the green revolution success. After a long time of disinterest in the agriculture sector in Africa, several voices arise now in favour of greater efforts towards this sector. Several studies tend to show the crucial role of agriculture in African countries' growth and highlight the huge need of increasing the productivity in this sector. If an increase in agriculture productivity requires both an expansion of irrigated areas and the adoption of high-yield varieties, those innovations and their high development could be the source of negative health (and environmental) effects. Using a mega-analysis, this paper highlights first the links between health, disease and development and then agricultural productivity. The literature review shows that the negative effect of bad health was not systematically checked, and that the intensity of this effect depends on disease and also on the work productivity and the existence or not of a coping process. The second part of the paper focuses on the development of high-intensive agriculture as a risk factor for farmers' and rural inhabitants' health. This survey shows that whether irrigation and fertiliser and pest intensive use could be considered highly health (and environmental) risk factors, and appropriate control measures (such as systematic maintenance of irrigation canals, alternate wetting and drying of irrigated fields or integrated pest management) considerably reduce this risk, while at the same time, increase the agriculture productivity.
Keywords: African Research